Percentage of Mitral Valve Replacement Patients on Warfarin within the Therapeutic Range of International Normalized Ratio (INR) - Singh, Amit Kumar; Man Singh Pradhan, Pranil; Shah, Rajesh Kumar; Mahaseth, Aditya (Nepalese Heart Journal, 2025)
Background: Nepal has a high prevalence of rheumatic heart disease and many patients undergo metallic valve replacement. Most of the time, the replaced valve is the mitral valve. It is more prone to getting stuck than a prosthetic aortic valve. It also requires a higher INR value to maintain the patient in the therapeutic range. There is limited data regarding patients’ time in the therapeutic range (TTR). This study will help better manage such patients and know the shortcomings in management. Methods: A total of 70 mitral valve replacement patients fulfilling the inclusion criteria having at least 3 months regular visit for INR underwent Rosendaal method to estimate TTR. Results: The study conducted at Shahid Gangalal National Heart Centre, Janakpurdham, showed that only 58.5% of patients were within the INR therapeutic range. The most frequent dose was approximately 6 mg with almost all patients requiring dose variation not in whole numbers but in decimals as daily warfarin dose. Conclusions: A significant proportion of patients remain outside the therapeutic range. Dosing of warfarin is in decimal. This suggests a need for lower-dose warfarin formulations like 0.5mg to help patients staying in therapeutic INR. For uniform INR report throughout country, national level thromboplastin has to be introduced. Genetic study inclusion in warfarin dose will help in accuracy of dosage. A separate INR clinic will further improve patient care.